Testing and Diagnosing Dyslexia in Adolescents – Focused on Phonemic Awareness - Žovinec, Erik; Duchovičová, Jana; Sender, Barbora (Journal of Education Culture and Society, 2023)
Aim. Phonetic deficits are one of the core language-cognitive symptoms at cognitive level aetiology of dyslexia in variety languages and orthographies. The presented study examines possibilities of diagnosis of phonological deficits in the Slovak language (similar to Czech and Polish grapheme-phoneme rules) in students at upper secondary schools. The comparison of 237 non-dyslectics and 149 dyslectics in upper secondary schools brings new stimulus for diagnostic procedures at counselling centres. Methods. Four phonemic awareness tests for upper secondary school students (aged 15-20 years) were developed. The testing tasks included tasks on phoneme analysis/segmenting in words and non-words (10), phoneme synthesis/blending in words and non-words (10), phoneme transposition in words and non-words (8), and phoneme elision in non-words (8). Results. Dyslectics achieved a lower average score in phonemic awareness tests than non-dyslectics. First and second year students (aged 15-17 years) achieved similar average scores, but third and fourth year students (aged 17-20 years) achieved lower results. The t-statistic for the phonological analysis tests was 2.827 with df 56.259 and a p-value of 0.007, indicating a significant difference between the groups under study. The t-statistic for the phonological synthesis tests was -2.568 with df 284 and a p-value of 0.011, also indicating a significant difference between the groups. The t-statistics for the phonological transposition and elision tests indicate that there is no significant difference between the dyslexic and non-dyslexic group. Conclusion. The study brought several inspirations for the tasks and tests that can be used in the diagnosis and re-diagnosis of dyslexia, specifically for adolescents.